2009
DOI: 10.1007/s12032-009-9172-5
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence Hodgkin’s lymphoma and colonic adenocarcinoma: a case report

Abstract: We present the case of a patient having colonic adenocarcinoma and also incidentally found Hodgkin's lymphoma which involved a single mesenteric lymph node dissected from the sigmoidal resection performed for colonic carcinoma. The disease was confirmed with the removal of right posterior cervical lymph node. Coexistence of colonic carcinoma and lymphoma in the same patient is an uncommon event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the simultaneous occurrence of HL and hematological malignancies such as chronic lymphocytic leukemia, peripheral T-cell lymphoma, or diffuse large B-cell lymphoma [21][22][23][24][25]. Also, Hodgkin lymphoma can be seen as synchronous or metachronous with solid tumors such as testicular germ cell neoplasm, laryngeal squamous cell carcinoma, colon carcinoma, gastric adenocarcinoma and pleomorphic adenoma [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological examination of the neck dissection specimen revealed coincidental mixed cellular type HL [15]. Several authors reported that affecting mesenteric lymph nodes with HL was discovered incidentally at laparotomy for colon carcinoma in the same patient [16][17][18].…”
Section: Discussionmentioning
confidence: 99%